Antibacterial Effectivity of Javanese Turmeric (Curcuma zanthorrhiza) Compared to Red Ginger (Zingiber officinale var. rubrum) Extracts against Enterococcus faecalis - Martono, Martono; Pang, Vincent; Florenly, Florenly (e-GiGi, 2025)
Abstract: Enterococcus faecalis contributes to a number of dental infections, including root canal infections, periodontitis, and peri-implantitis and shows antibiotic resistance. Javanese turmeric (Curcuma zanthorrhiza) and red ginger (Zingiber officinale var. rubrum), rich in antibacterial compounds, offer potential alternatives. This study explores their effectiveness at two concentrations against E. faecalis. This experimental study analyzed the phytochemical compounds qualitatively, which play an important role as antibacterial against Enterococcus faecalis. Afterwards, both extracts at 50% and 75% concentrations were prepared, tested on bacterial cultures, and compared to a 2.5% NaOCl solution. Inhibition zones were measured, and data were analyzed statistically to compare the effectivity of each extract group. The results showed that Javanese turmeric extract (JTE) (50% and 75%) had higher effectiveness, averaging 12.20±0.23 and 14.44±0.39, respectively. Red ginger extract (RGE) (50% and 75%) inhibited Enterococcus faecalis with a lower inhibition zone of 10.76±0.38 and 13.64±0.55. The 2.5% NaOCl control group had an inhibition zone of 13.38±0.79. When using the ANOVA and post-hoc Tukey statistical analysis, JTE 50% and RGE 50% showed the most significant differences compared to other groups (p<0.05). The inhibition power increased in higher concentration groups. In conclusion, Javanese turmeric extract and red ginger extract 75% are the most significant inhibitors of Enterococcus faecalis. The control group does not has significant differences with RGE 75% treatment groups, suggesting similar effectivity to the control. Keywords: Curcuma zanthorrhiza; Zingiber officinale var rubrum; Enterococcus faecalis; antibacterial effect